Life Expectancy slowdown in V4 countries - Gogola, Ján (Corvinus University of Budapest, 2020)
The main objective of the contribution is to show trends in life expectancy in Visegrád 4 (V4) countries in recent years. Life expectancy has increased in all OECD countries over the last few decades. Whilst life expectancy has increased steadily over time, there has been a slowdown in recent years. The aim of our contribution is to describe trends in recent years and then try to find which factors are behind these trends. To examine the slowdown in life expectancy improvements in recent years, changes in life expectancy at birth between 2002 and 2017 were chosen. Generally we can say that causes of this slowdown in life expectancy gains are multifaceted. Mortality at older ages is the primary driver of slowing improvements in life expectancy. It is unclear whether the current slowdown in mortality improvements is long-term trend or not. The slowdown has not been observed for long enough for statistical analysis to determine whether it will continue
Zpomalení růstu průměrné délky života v zemích V4
Keywords: Life expectancy at birth, V4 countries; Očekávaná délka života při narození, země Visegrádské 4